PENERAPAN METODE UMMI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA SISWA KELAS V DI MADRASAH IBTIDAIYAH MODERN MUTIARA IMAN KECAMATAN NGUNUT KABUPATEN TULUNGAGUNG - Isna Khusnul Masruroh; Dyah Aris Susanti; Nina Sultonurohmah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to explain how the Ummi method is used to improve fifth-grade students' Quran reading skills at MI Modern Mutiara Iman Ngunut Tulungagung, and to identify the factors that support and hinder its implementation, as well as the results of applying this method. This study uses a qualitative approach with a case study research type. Data was collected through observation, in-depth interviews, and document gathering. Data analysis is done interactively through data reduction, data presentation, and drawing conclusions, and its validity is tested using source triangulation and techniques. The research results show that the Ummi method was applied in a planned way through teacher training, using a multi-volume learning system, applying the talaqqi and musyafahah methods, and implementing continuous learning evaluation. The supporting factors include certified teachers, available learning materials, adequate school facilities, a good learning environment, and support from parents. At the same time, factors that slow things down include differences in students' abilities, lack of support for learning at home, and inconsistent study motivation. Using the Ummi method has been proven effective in improving students' ability to read the Quran, as seen from increased reading fluency, accurate pronunciation of letters, better understanding of tajwid rules, and improved confidence and discipline in studying the Quran. This finding shows that Ummi's method can be used as an alternative way to teach the Quran in elementary Islamic schools.